2013
DOI: 10.4103/0377-4929.120359
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of non-invasive models for liver fibrosis in chronic hepatitis B virus related liver disease patients in resource limited settings

Abstract: Out of the three indices, APRI index with a NPV of 95% appeared to be a better model for excluding significant liver fibrosis while FIB-4 with a PPV of 61% showed fair correlation with significant fibrosis. Thus, these two non-invasive models for predicting of liver fibrosis, namely APRI and FIB-4, can be utilized in combination as screening tools in monitoring of CHB patients, especially in resource limiting settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Sensitivity analysis was conducted by sequentially excluding some special studies (with small sample size, bigger cut-off value) [20, 27]. The pooled results did not alter, indicating the results were stable.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity analysis was conducted by sequentially excluding some special studies (with small sample size, bigger cut-off value) [20, 27]. The pooled results did not alter, indicating the results were stable.…”
Section: Resultsmentioning
confidence: 99%
“…The study found NPV of APRI to be 95% for excluding significant liver fibrosis, while FIB-4 with a PPV of 61% showed fair correlation with significant fibrosis. 32 Moreover, the World Health Organization recommend the use of APRI for estimating liver fibrosis in patients with CHB, where limited availability of resources was an issue. 24 The next non-invasive parameter was GPR, which was developed in France and Western Africa to evaluate fibrosis in subjects with HBV, particularly in low-resource settings.…”
Section: Discussionmentioning
confidence: 99%
“…The study found NPV of APRI to be 95% for excluding significant liver fibrosis, while FIB-4 with a PPV of 61% showed fair correlation with significant fibrosis. 32 Moreover, the World Health Organization recommend the use of APRI for estimating liver fibrosis in patients with CHB, where limited availability of resources was an issue. 24…”
Section: Discussionmentioning
confidence: 99%
“…Shrivastava et al [ 85 ] concluded that APRI and FIB-4 can be utilized in combination as a screening tool to monitor CHB patients, especially in resource-limited settings.…”
Section: Introductionmentioning
confidence: 99%